Delayed stormflow generation in a semi-humid forested watershed controlled by soil water storage and groundwater dynamics - Z. Cui; F. Tian (Hydrology and Earth System Sciences)
Recent research by Cui et al. (2024) identified a distinct threshold governing bimodal rainfall–runoff events in a semi-humid mountainous forested watershed in north China, where delayed stormflow was influenced by shallow groundwater dynamics. Building on these findings, this study further investigates the mechanisms driving these bimodal events, focusing on the interactions between soil water content (SWC) and groundwater level (GWL) during storm events. The results show that delayed stormflow is primarily governed by the interplay between SWC and GWL. Delayed stormflow is initiated when SWC exceeds the soil's water storage capacity, and its timing and magnitude are further modulated by GWL fluctuations. During rainfall, SWC increases rapidly but stabilizes after the rain ceases if the soil's water-holding capacity is not reached. Conversely, when SWC surpasses the storage capacity, the excess rainwater infiltrates into the subsurface, recharging groundwater and causing a gradual rise in GWL. As GWL rises, enhanced hydraulic conductivity facilitates the lateral movement of shallow groundwater towards the stream channel, generating delayed stormflow. When the GWL surpasses a critical threshold, its responses across the watershed become synchronized, significantly boosting groundwater discharge and reducing lag times. In extreme cases, the delayed stormflow peak converges with the direct stormflow peak. These findings enhance the understanding of delayed stormflow mechanisms in semi-humid mountainous watersheds and refine runoff generation theories by elucidating the threshold-driven processes governing the timing and magnitude of delayed stormflow.